1992
DOI: 10.2135/cropsci1992.0011183x003200040012x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity for RFLPs in European Maize Inbreds: I. Relation to Performance of Flint ✕ Dent Crosses for Forage Traits

Abstract: Restriction fragment length polymorphisms (RFLPs) have been proposed as a tool for assigning inbreds to heterotic groups and predicting heterosis and performance of single‐cross hybrids in maize (Zea mays L.). Such use was evaluated in 11 flint and 11 dent inbred lines from the European maize germplasm and in 66 F1 hybrids produced between them according to an incomplete factorial mating scheme. Inbreds and hybrids were evaluated for 12 forage yield and quality traits in three and six environments, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0
3

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 0 publications
6
23
0
3
Order By: Relevance
“…However, the magnitude of correlation coefficients determined between GDs of line tester combinations with F 1 yield and yield MPH in this study was not large enough; therefore, it is of less utility for the perdition of hybrid performance. Similar results were reported by a number of investigators with different types of crops including maize (Boppenmaier et al 1992;Martin et al 1995;Xu et al 2002;Barbosa et al 2003;Oliveira et al 2004).…”
Section: Discussionsupporting
confidence: 86%
“…However, the magnitude of correlation coefficients determined between GDs of line tester combinations with F 1 yield and yield MPH in this study was not large enough; therefore, it is of less utility for the perdition of hybrid performance. Similar results were reported by a number of investigators with different types of crops including maize (Boppenmaier et al 1992;Martin et al 1995;Xu et al 2002;Barbosa et al 2003;Oliveira et al 2004).…”
Section: Discussionsupporting
confidence: 86%
“…There was no correlation between GD and F1 grain yield, MPH, HPH and SCA when the GD was C0.77. In previous studies, the predictive value of GD was reported for crosses in temperate maize among genetically related lines than among more distantly related lines (Godshalk et al 1990;Boppenmeier et al 1992;Melchinger 1993;Ajmone Marsan et al 1998) and similar findings were reported in tropical maize (Benchimol et al 2000). In this study, the high correlation of GD with F1 grain yield and with SCA in specific subsets of crosses having a narrower range of GD shows that GD can be put to practical use in predicting hybrid performance.…”
Section: Subsets Of Crossessupporting
confidence: 85%
“…The analysis of variance (ANOVA) for agronomic traits was performed on the data of each environment separately, followed by a combined analysis across environments based on the lattice adjusted entry means according to Cochran & Cox (1957) and following Boppenmaier et al (1992), using PLABSTAT 2O (Utz, 2001). All effects in the statistical model were considered random.…”
Section: Data Analysesmentioning
confidence: 99%